2018
DOI: 10.1097/mnh.0000000000000396
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic sources and physio-pathological functions of soluble (pro)renin receptor

Abstract: sPRR is a 28 kDa product of PRR cleavage via S1P-mediated protease activity. Not only does sPRR regulate renal tubular water transport, but it also mediates pathogenic responses to renal cellular injury. sPRR is likely involved in a wide range of physio-pathological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In addition to the use of PRR as a tissue biomarker for CRC detection and prognosis, we aimed to complementarily measure it in CRC patients’ plasma samples to explore its potential as a CRC biomarker in liquid biopsies. In fact, PRR is a membrane protein expressed in several tissues that, after cleavage, can be released to the extracellular space and can be detected in plasma and urine from subjects with different physiological and pathological conditions [28,30,55,56]. Shibayama et al recently reported higher sPRR levels in patients with pancreatic ductal adenocarcinoma than in healthy controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use of PRR as a tissue biomarker for CRC detection and prognosis, we aimed to complementarily measure it in CRC patients’ plasma samples to explore its potential as a CRC biomarker in liquid biopsies. In fact, PRR is a membrane protein expressed in several tissues that, after cleavage, can be released to the extracellular space and can be detected in plasma and urine from subjects with different physiological and pathological conditions [28,30,55,56]. Shibayama et al recently reported higher sPRR levels in patients with pancreatic ductal adenocarcinoma than in healthy controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PRR can interact with the membrane receptor complex of the Wnt/␤-catenin pathway and with vacuolar-type H ϩ -ATPase (9,38). Previous studies have shown that kidney PRR and brain PRR are essential in the maintenance of fluid homeostasis and blood pressure (21,22,37,40,41) and that sPRR participates in fluid homeostasis and chronic kidney diseases (15,16,24,61). However, whether there is a link between sPRR and the local RAS and blood pressure is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be linked to a well-described proteolytic cleavage event in the Golgi apparatus that produces an N-terminal and a C-terminal fragment (NTF and CTF, respectively) ( Cousin et al. , 2009 ; Zhu and Yang, 2018 ). While mosaic analysis in flies demonstrated that the NTF from the hemolymph or from the secretion by neighboring cells can localize to PCP domains ( Hermle et al.…”
Section: Introductionmentioning
confidence: 99%